Stone prism encased concrete-filled steel tube columns subjected to axial compression. (October 2021) - Ye, Yong; Liu, Yang; Guo, Zi-Xiong; Chicchi, Rachel
Abstract: A new type of concrete-filled steel tube (CFST) structural member is proposed by replacing the central portion of the infilled concrete with a stone prism. The mechanical behavior of the stone prism encased concrete-filled steel tube (SCFST) members under axial compression was studied through experimental testing. A total of twenty-four stub columns, including eighteen SCFST specimens and six CFST specimens, were subjected to axial compression until failure occurred. The primary parameters considered were the size of the stone prism ( s = 75 mm, 100 mm or 125 mm), wall-thickness of the steel tube ( t = 6.0 mm, 8.0 mm or 12.0 mm), and concrete strength ( f cu = 62.3 MPa or 107.0 MPa). Test results demonstrated the composite actions between the three parts of the member, which significantly enhanced the load-carrying capacity of the SCFST column. The effect of the parameters on the failure mechanism, load-carrying capacity, load versus deformation response, and ductility of the SCFST specimens was researched. Meanwhile, the experimentally obtained axial compressive strength of each SCFST specimen was compared with predicted strengths obtained by adopting the formulae from currently available design codes for conventional CFST columns. These design codes could not precisely predict the load-carrying capacity of SCFST stub columns, and an improved model was proposed.